2022
DOI: 10.12998/wjcc.v10.i15.4964
|View full text |Cite
|
Sign up to set email alerts
|

Male metaplastic breast cancer with poor prognosis: A case report

Abstract: BACKGROUND Metaplastic breast cancer (MBC) is a rare subtype of breast cancer. They constitute less than 1% of breast cancer cases and are much rarer in males. There are few reports of MBC because of its rarity. MBC, an aggressive type of cancer, is refractory to common treatment modalities of breast cancer and has a poor prognosis. CASE SUMMARY We report a case of MBC in a 78-year-old man. He visited our clinic with a palpable mass on the left breast with no masses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…1,2 Excluding the lowgrade adenosquamous and fibromatosis-like variants, MBCs are often aggressive and chemoresistant. 2,3 Per literature review, there are only a handful of reported cases of male MBC [10][11][12][13][14][15] and to our knowledge, there is no recorded evidence of a male spindle cell breast cancer subtype. Male breast cancer is very rare, accounting for less than 1% of all cancers in men and less than 1% of all breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Excluding the lowgrade adenosquamous and fibromatosis-like variants, MBCs are often aggressive and chemoresistant. 2,3 Per literature review, there are only a handful of reported cases of male MBC [10][11][12][13][14][15] and to our knowledge, there is no recorded evidence of a male spindle cell breast cancer subtype. Male breast cancer is very rare, accounting for less than 1% of all cancers in men and less than 1% of all breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The current understanding of metaplastic breast cancer involves comprehensive molecular profiling and histological evaluation to identify potential therapeutic targets. However, due to the rarity of the disease, clinical trials and evidence-based treatment guidelines specific to metaplastic breast cancer in male patients are scarce [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%